Proposal to improve the productivity of t-shirts through lean manufacturing tools in an SME of the textile sector - Reyna Medina, Elizabeth (2025)
Taking into account the implementation of lean methodologies will be key to achieve a significant change in the productivity of companies in the textile industry as this sector is currently facing increasing competitiveness. This article explains an improvement proposal to increase productivity in the manufacture of t-shirts in a textile SME located in Lima Peru by implementing Lean Manufacturing tools and promoting a balanced production line to solve the high percentage of products with defects and the lack of control and monitoring in the production process. A diagnosis of the current situation was obtained and the operations with the greatest slack were determined through the elaboration of a time study and the application of Lean tools. To solve the problems identified 5S tools and standardized work were implemented to achieve optimal distribution avoid unnecessary transportation and achieve a standardized inspection methodology. In addition the implementation of line balancing reduced the number of workstations from 14 to 7 stations combining the operations of the production line. The improvement proposal was validated in Arena software by simulating the current scenario and the proposed scenario which resulted in a 47.54% increase in productivity.